HOMESIDE—A home‐based family caregiver‐delivered music and reading intervention for people living with dementia: A randomised controlled trial. (31st December 2021) - Baker, Felicity; Odell‐Miller, Helen; Wosch, Thomas; Stensaeth, Karette; Bukowska, Anna; Clark, Imogen
Abstract: Background: Pharmacological interventions to address behavioural and psychological symptoms of dementia (BPSD) can have undesirable side effects, therefore non‐pharmacological approaches to managing symptoms may be preferable. Past studies show that music therapy can reduce BPSD, and other studies have explored how formal caregivers use music in their caring roles. However, no studies have examined the effects on BPSD of music interventions delivered by informal caregivers (CGs) in the home setting. Our project addresses the need for improved informal care by training cohabiting family CGs to implement music interventions that target BPSD, and the quality of life (QoL) and well‐being of people with dementia and CGs. Methods: An international three‐arm parallel‐group randomised controlled trial has so far randomised 130 of the target 495 dyads from Australia, Germany, UK, Poland and Norway. Dyads are randomised equally to standard care (SC), a home‐based music programme plus SC, or a home‐based reading programme plus SC for 12 weeks. The primary outcome is BPSD of people with dementia (measured using the Neuropsychiatric Inventory‐Questionnaire). Secondary outcomes examine relationship quality between CG and people with dementia, depression, resilience, competence, QoL for CG and QoL for people with dementia. Outcomes are collected at baseline, at the end of the 12‐week intervention and at 6 months post randomisation. Resource Utilisation in Dementia captures economic data across the life of the intervention and at 6‐month follow‐up. Our presentation will briefly outline the study protocol and describe the caregiver training protocol and interventions in detail with video footage illustrating how the intervention looks in practice.